Regulasi Diri terhadap Gangguan Perilaku Internet Gaming - Inta Susanti; Budi Utomo; Makhfudli Makhfudli (Journal of Telenursing (JOTING), 2021)
This study aims to determine the effect of self-regulation on internet gaming behavior. The method used is a systematic review of seven databases (Scopus, Sage, ScienceDirect, CINAHL, ProQuest, Cambridge, Pubmed) published from 2017 to 2020. The results show that there is a significant relationship between self-regulation and internet gaming behavior disorders. Low regulation was associated with more excellent reports of impaired internet gaming behavior, self-regulation directly impacting internet gaming behavior, or mediator between determinants and internet gaming behavior. Self-development strategies, self-monitoring interventions and self-instruction strategies are the dominant types of self-regulation techniques for some studies. In conclusion, the intervention of increasing self-regulation can prevent internet gaming behavior disorder. Keywords: Online Game, Internet Gaming Disorder, Internet Gaming Behavior, Self Regulation